"I’m strong within myself": Gender, class and emotional capital in childcare - Andrew, Yarrow (British Journal of Sociology of Education, 2015)
Emotions have received increasing attention in educational circles in the last decade. Drawing on Bourdieu, feminist scholars use emotional capital to illustrate the ways gendered inequalities can compound the disadvantages of social class. This paper examines relationships within childcare services in Australia, showing how emotional capital functions as a resource for staff. Data from interviews with childcare staff illustrate key aspects of emotional capital, such as reflexivity, resilience and embodiment. Findings show that investing in emotional capital is the key to a long-lasting commitment to childcare work, and should be valued accordingly. © 2013 Taylor & Francis.
Keywords: 2000 à aujourd'hui; 2010-2019; australie; capital émotionnel; care; discipline; maternité; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; service de garde; sociologie; thématiques; travail; travail du care

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Le care : éthique féministe actuelle - Bourgault, Sophie; Perreault, Julie (Les éditions du remue-ménage, 2015)
Cet ouvrage présente une réflexion pluridisciplinaire sur l'éthique féministe du care. Élaborée par Carol Gilligan dans In a Different Voice en 1982, cette «éthique de la sollicitude» a été très prisée dans les années 1980. Plus récemment, nous assistons à l'émergence d'une enthousiaste seconde génération de théoricien.ne.s du care qui y voient un terreau fertile pour réfléchir aux oppressions liées à la division genrée du travail.Comment ce renouveau se traduit-il? Quels sont les enjeux éthiques, politiques et épistémologiques que permet de mettre en lumière cette approche? Le care équivaut-il essentiellement au travail de soin effectué en majorité par les femmes, ou comprend-il l'ensemble des services domestiques, affectifs et sexuels fournis dans un rapport d'interdépendance?L'originalité de ce premier ouvrage faisant le point sur la question au Québec tient entre autres à son souci constant de débarrasser le care du sentimentalisme qu'on lui a souvent reproché, et surtout, de le réinvestir de tout son potentiel critique et féministe.Avec des textes de Bettina Bergo, Agnès Berthelot-Raffard, Sophie Bourgault, Sophie Cloutier, Marjolaine Deschênes, Stéphanie Gaudet, Naïma Hamrouni, Mariko Konishi, Monique Lanoix, Patricia Paperman et Julie Perreault.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; discours dominant; division sexuelle du travail; inégalités; patriarcat; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; santé; santé mentale; systèmes d'oppressions; thématiques; travail

Food and femininity - Cairns, Kate; Johnston, Josée (Bloomsbury Academic, 2015)
"Over the space of a few generations, women's relationship with food has changed dramatically. Yet – despite significant advances in gender equality – food and femininity remain closely connected in the public imagination as well as the emotional lives of women. While women encounter food-related pressures and pleasures as individuals, the social challenge to perform food femininities remains: as the nurturing mother, the talented home cook, the conscientious consumer, the svelte and health-savvy eater. In Food and Femininity, Kate Cairns and Josée Johnston explore these complex and often emotionally-charged tensions to demonstrate that food is essential to the understanding of femininity today. Drawing on extensive qualitative research in Toronto, they present the voices of over 100 food-oriented men and women from a range of race and class backgrounds. Their research reveals gendered expectations to purchase, prepare, and enjoy food within the context of time crunches, budget restrictions, political commitments, and the pressure to manage health and body weight. The book analyses how women navigate multiple aspects of foodwork for themselves and others, from planning meals, grocery shopping, and feeding children, to navigating conflicting preferences, nutritional and ethical advice, and the often-inequitable division of household labour. What emerges is a world in which women's choices continue to be closely scrutinized – a world where 'failing' at food is still perceived as a failure of femininity. A compelling rethink of contemporary femininity, this is an indispensable read for anyone interested in the sociology of food, gender studies and consumer culture."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; corps féminin; cours; discipline; inégalités; ontario; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2264; sociologie; systèmes d'oppressions; thématiques; toronto; travail

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Care, environnement et éthique globale - Laugier, Sandra (Cahiers du Genre, 2015)
Cet article vise à mettre en évidence la puissance transformatrice des éthiques féministes du care pour les questions environnementales, et réciproquement, à montrer comment la question environnementale est le lieu présent de redéfinition des enjeux du care . En valorisant des caractéristiques morales identifiées comme féminines — l’attention, le souci des autres — l’éthique du care a contribué à placer la vulnérabilité au cœur de la morale, mais a aussi déplacé et élargi son champ. Ce que le care peut nous apprendre sur la question environnementale, c’est que le développement de nos sociétés riches occidentales n’a été possible que par leur dépendance par rapport à une nature, à des ressources — des animaux et des humains. La crise climatique est l’occasion de repenser l’idée de développement durable à partir du care .
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; care; cours; discipline; inégalités; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; écoféminisme

Que horas ela volta? = Une seconde mère (Memento Films, 2015)
La visite de sa fille, adolescente fière, perturbe le quotidien d'une domestique de Sao Paulo partageant la demeure de ses employeurs. [Médiafilm].
Place: Paris, France
Keywords: amériques; brésil; care; cinéma; communication; cours; discipline; film; maternité; pol4022; premier cycle; régions géographiques; thématiques; travail; travail domestique

The mask you live in (Kanopy Streaming, 2015)
HE MASK YOU LIVE IN follows boys and young men as they struggle to stay true to themselves while negotiating America’s narrow definition of masculinity. Pressured by the media, their peer group, and even the adults in their lives, our protagonists confront messages encouraging them to disconnect from their emotions, devalue authentic friendships, objectify and degrade women, and resolve conflicts through violence. These gender stereotypes interconnect with race, class, and circumstance, creating a maze of identity issues boys and young men must navigate to become “real” men. Experts in neuroscience, psychology, sociology, sports, education, and media also weigh in, offering empirical evidence of the “boy crisis” and tactics to combat it. The Mask You Live In ultimately illustrates how we, as a society, can raise a healthier generation of boys and young men.
Place: San Francisco, California, USA
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cinéma; communication; cours; discipline; documentaire; féminisme pop; histoire et politique; intersectionnalité; masculinité; premier cycle; périodes historiques; représentation des hommes; régions géographiques; sex2283; sexualité; thématiques; travail; violences; états-unis

Des femmes respectables : classe et genre en milieu populaire - Skeggs, Beverley (Agone, 2015)
La matière première de ce livre est une série d'entretiens menés par Beverley Skeggs avec quatre-vingt-trois jeunes femmes issues de la classe ouvrière anglaise, inscrites à une formation d'aide à la personne et travaillées par leur propre respectabilité. Abordant leur rapport à la sexualité, à la classe ou au féminisme, cet ouvrage vient apporter un prolongement essentiel aux travaux de Pierre Bourdieu et de Paul Willis.
Édition originale : B. Skeggs, Formations of Class & Gender. Becoming Respectable, Sage, 1997
Keywords: 1900-1999; 1980-1989; 1990-1999; analyse de discours; angleterre; approches et analyses; care; classe ouvrière; classe sociale; cours; cultural studies; cycles supérieurs; discipline; ethnographie; europe; fem7000; fémininité; féminisme marxiste; histoire et politique; point de vue situé; périodes historiques; rapports sociaux de sexe; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sciences sociales; sexualité; sociologie; thématiques; épistémologie